1987
DOI: 10.1002/chin.198735345
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Guanine 7‐Oxide, an Antitumor Antibiotic from Streptomyces Species.

Abstract: Phenacyl bromide (I) is converted to the phenacylamines (III) which react with the pyrimidone (IV) to yield the N‐disubstituted products (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…l-N, 3-N, the primary amino acid group in position 6, and the two imidazole nitrogens, It is known (19,20) that direct chemical N-oxide formation of 3-N and imidazole nitrogens is not possible and there is no report of such N-oxide formation with liver microsomal fractions. On the other hand, loN-oxide formation by direct chemical oxidation is well known (21,22), as well as the oxidative formation of hydroxylamines from primary aromatic amines (23).…”
Section: Discussionmentioning
confidence: 99%
“…l-N, 3-N, the primary amino acid group in position 6, and the two imidazole nitrogens, It is known (19,20) that direct chemical N-oxide formation of 3-N and imidazole nitrogens is not possible and there is no report of such N-oxide formation with liver microsomal fractions. On the other hand, loN-oxide formation by direct chemical oxidation is well known (21,22), as well as the oxidative formation of hydroxylamines from primary aromatic amines (23).…”
Section: Discussionmentioning
confidence: 99%
“…by Jackson and coworkers, also demonstrated that compound 207 was converted into guanosine 7-oxide 5′-triphosphate within sensitive cells and this led to the inhibition of cellular protein synthesis. [173] Nishii and coworkers reported a weak antimicrobial activity of the nucleoside analogue 208 . Nucleoside N -oxide 208 also caused apparent inhibition of L5178Y mouse leukemia cell in culture with IC 50 = 0.60 mg/mL.…”
Section: Case Studies Of Heterocyclic N-oxide Drugs and Emerging Bmentioning
confidence: 99%
“…[173] This strategy commenced with the reaction of the phenacylamines 214 with 2-amino-6-chloro-5-nitro-4(3 H )-pyrimidinone ( 215 ) in the presence of NaOH to afford compound 216 , Further treatment with NaOH yielded protected guanine 7-oxide 217 , which could be deprotected with sulfuric acid to afford the desired N -oxide 207 . It should be noted that direct oxidation of guanine did not lead to this compound, but rather afforded guanine-3 N - oxide.…”
Section: Case Studies Of Heterocyclic N-oxide Drugs and Emerging Bmentioning
confidence: 99%
See 1 more Smart Citation